Religiøs argumentation som religionsfænomenologisk forskningsområde - Aktor, Mikael (Religionsvidenskabeligt Tidsskrift, 1992)
This article is a reflection on the specific character of religious assertations and religious arguments. The basic point of view is that these religious practices should not be investigated as isolated religious phenomena sui generis, but on the contrary, that they are conditioned by and derived from common linguistic and epistemological practices that relate to the concrete material world. Religious assertations join together finction and description of the world, whereas religious arguments refer todata which are either quasi-empiric (a holy scripture for instance) or quasi-public (a mystical experience for instance). in four text examples these derivations are investigated in the light of a two-component definition of religion, which stresses the concept of an essential difference as well as the concept of a possibility of a passage to an fro between essentially differenct categories.